Penggunaan Media Transformer Angka Dalam Pembelajaran Matematika Materi Mengenal Angka Di Kelas Rendah Sekolah Dasar - Defa, Defa (Universitas Negeri Padang, 2024)
This Best practice paper is to develop learning media in the Lower Grades in mathematics. This paper focuses on the initial class that has just entered a new school in elementary school, namely students at the age stage between 7-8 years. The background in writing this paper is how the learning media used in grade 1 is learning while playing. Students in their first grade enter elementary school, it must be a place they enjoy as it is for children who have attended kindergarten or early childhood education. During kindergarten and early childhood, children are more inclined to play while learning. This was done to attract students in grade 1 to lose the feeling of playing at PAUD/Kindergarten. The author makes a learning media that is